PENGARUH KARAKTERISTIK PERUSAHAAN, CAPITAL INTENSITY DAN SALES GROWTH TERHADAP AGRESIVITAS PAJAK - Adhitya Putri Pratiwi; Dewi Wulandari (CV. Denasya Smart Publisher, 2026)
This study aims to analyze the effect of firm characteristics, capital intensity, and sales growth on tax aggressiveness in companies listed in the IDX30 index on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data derived from companies’ financial statements and annual reports. The sample was determined using a purposive sampling technique, resulting in 13 companies observed over five years, yielding 65 panel data observations. The analysis was conducted using panel data regression with the Random Effect model processed through EViews 12. The results indicate that simultaneously, firm characteristics, capital intensity, and sales growth have an effect on tax aggressiveness (sig. 0.000). Partially, firm characteristics (sig. 0.0129) and capital intensity (sig. 0.0001) have a significant effect on tax aggressiveness, while sales growth does not have a significant effect on tax aggressiveness (sig. 0.1085).